2014
DOI: 10.1120/jacmp.v15i4.4835
|View full text |Cite|
|
Sign up to set email alerts
|

Using the ACR CT accreditation phantom for routine image quality assurance on both CT and CBCT imaging systems in a radiotherapy environment

Abstract: Image‐guided radiation therapy using cone‐beam computed tomography (CBCT) is becoming routine practice in modern radiation therapy. The purpose of this work was to develop an imaging QA program for CT and CBCT units in our department, based on the American College of Radiology (ACR) CT accreditation phantom. The phantom has four testing modules, permitting one to test CT number accuracy, slice width, low contrast resolution, image uniformity, in‐plane distance accuracy, and high‐contrast resolution reproducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Target detectability of CBCT is a very important image quality metric to achieve a high level of patient positioning and treatment accuracy 10, 11, 12, 13. In spite of the increasing use of CBCT to verify and correct patient setup, the contrast resolution of CBCT in delineating soft tissue structures is lower than that of MDCT 14, 15. MDCT has approximately 3 Hounsfield units (HU) contrast resolution, while CBCT allows a contrast resolution of 10 HU 16.…”
Section: Introductionmentioning
confidence: 99%
“…Target detectability of CBCT is a very important image quality metric to achieve a high level of patient positioning and treatment accuracy 10, 11, 12, 13. In spite of the increasing use of CBCT to verify and correct patient setup, the contrast resolution of CBCT in delineating soft tissue structures is lower than that of MDCT 14, 15. MDCT has approximately 3 Hounsfield units (HU) contrast resolution, while CBCT allows a contrast resolution of 10 HU 16.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to their recommendations for the volume, Hobson et al [16] reported comparative recommendations for CBCT, and state that due to the higher fraction of scatter encountered in cone beam imaging, the center to edge HU variation in reconstructed image slices should be more generous, namely within ±22 HU.…”
Section: Resultsmentioning
confidence: 95%
“…Hobson et al [16], recently published a study using the ACR CT accreditation phantom on CBCT systems, and proposed image quality recommendations for CBCT, after comparing 4 different radiation therapy CBCT devices. The Hobson report states that due to the high variability introduced by x-ray cone beams, the ± 7 HU limit for water is unrealistic, and therefore based on experimental measurements, suggest a range of ±16 HU for water in a reconstructed volume, and ±22 HU variation from center to edge in a coronal slice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACR Accreditation process [32], with modality specific accreditation programs and image review, establishes standards for image quality and also educates facilities on how to improve. There is evidence that there is improved image quality on examinations that follow accreditation specifications and participate in accreditation programs [23][24][25][26][27][28][29][30][31][32][33][34][35]. Site accreditation can provide assurance to patients and referring physicians that their facilities are meeting national requirements for adequacy of personnel, image protocols and image quality.…”
Section: Protocol Selection and Image Acquisitionmentioning
confidence: 99%